Dinamika Perekonomian Indonesia: sebuah Tinjauan Historis dari Sentralisasi ke Desentralisasi - Dedek Ayu; Mawarda Daulay; Retno Kaldianus Gowasa (Medan Resource Center, 2024)
Since Indonesia's independence in 1945, the nation has undergone profound economic transformations. The Indonesian economy has evolved significantly, shaped by factors like politics, society, and globalization. Employing a descriptive qualitative approach, this research gathers data from interviews, field notes, personal documents, and official records. Its qualitative nature aims to provide a detailed understanding of the phenomenon studied. The study examines centralization and decentralization concepts, tracing the historical shift from a centralized economy under Dutch colonialism to a decentralized system post-independence. The decentralization process, initiated during the reform era in 1998, aimed to distribute authority from the central government to regional authorities. This shift has impacted Indonesia's economic landscape, transitioning from a Jakarta-centric focus to a more regionally inclusive approach. During colonial rule, the Dutch managed Indonesia's economy centrally to serve their interests.